Basic Motivation and Human Behaviour Control, Affiliation and Self-expression - Kovac, Velibor Bobo (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book explores how and why humans are motivated to act in the ways that they do. The chapters examine the origins of a given action rather than their superficial appearance, which can often be misleading. Kovac integrates the existing knowledge of the field of motivation into a greater theoretical framework by adopting both analytical and holistic perspectives. This theoretical framework suggests that all human behaviour evolves from the three fundamental underlying tendencies connected to the concepts of control, affiliation and self-expression that are further modified by the mechanism of balanced dual tension. These tendencies are conceptualised as systems of interrelated psychological needs that guide and govern a variety of human actions. As such, this book should be useful to upper-level students and researchers of cognitive and social psychology and all scholars interested in human motivation. .